Cardiotoxicity of concomitant radiotherapy and trastuzumab for early breast cancer - Marinko, Tanja (Radiology and oncology (Ljubljana), 2014)
Background. Trastuzumab therapy given in combination with one of several chemotherapy regimens is currently considered the standard of care for the treatment of early-stage, human epidermal growth factor receptor-2 (HER2) -positive breast cancer. The treatment with trastuzumab is due to a significant impact on the survival part of the standard adjuvant treatment of patients with HER2-positive breast cancer. Patients treated with postoperative breast or chest wall irradiation receive trastuzumab concomitant with radiotherapy. In a small proportion of patients trastuzumab causes cardiotoxicity. Preclinical findings indicate a radiosensibilizing effect of trastuzumab in breast cancer cells, but it is not yet clear whether it radiosensibilizes cells of healthy tissues too.Conclusions. Special attention is required when left breast or left thoracic wall is irradiated in patient receiving trastuzumab, because long-term effects of the concurrent treatment with trastuzumab and radiotherapy are not yet known. In an era where more patients are surviving a diagnosis of breast cancer, better understanding and earlier detection of therapy-induced cardiac toxicity will be of paramount importance.
Keywords: breast; cardiotoxicity; dojke; early breast cancer; kardiotoksičnost; radioterapija; radiotherapy; rak (medicina); trastuzumab